1993
DOI: 10.1111/j.1600-0722.1993.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular forms and concentration of fibronectin and fibrin in human gingival crevicular fluid before and after periodontal treatment

Abstract: A total of 23 periodontitis‐affected sites from seven adults was selected for the study. Crevicular fluid (CF) samples were collected with paper strips before treatment (scaling, root planing, and curettage) and 2, 5, 10, 20, and 40 days after treatment. Each sample was eluted into sterile saline and two aliquots were drawn for gel electrophoresis: one for fibronectin and one for fibrin analysis. Peptides were transferred to nitrocellulose membranes, and molecules were detected by specific antibodies. The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Various studies by Talonpoika et al, [7,8] have shown that newly synthesized connective tissue components such as collagen type I and III and fibronectin are present at elevated levels in the GCF of treated sites which could be the reason for presence of TGF-β1 in GCF during the initial stages Post-surgery in this study. Postlethwaite et al, [9] had stated that TGF-β1 is present during initial phases of wound healing which could explain how TGF-β1 was detected in all sites following treatment as well.…”
Section: Discussionmentioning
confidence: 65%
“…Various studies by Talonpoika et al, [7,8] have shown that newly synthesized connective tissue components such as collagen type I and III and fibronectin are present at elevated levels in the GCF of treated sites which could be the reason for presence of TGF-β1 in GCF during the initial stages Post-surgery in this study. Postlethwaite et al, [9] had stated that TGF-β1 is present during initial phases of wound healing which could explain how TGF-β1 was detected in all sites following treatment as well.…”
Section: Discussionmentioning
confidence: 65%
“…Fibrin formation is common in inflamed sites [18,19] and fibrin shows a web-like appearance in SEM [20,21]. Fibrin has also been reported in inflammatory gingival exudate [22,23]. The lack of fibrin in the purulent crevicular exudate might be due to excessive quantities of the NET elastase [3], which efficiently digests fibrin [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…11 The degradation of cFn tends to be greater at diseased sites than at healthy or treated sites of periodontitis. 12 Mintz and Fives-Taylor 13 discovered that the level of cFn in individuals with adult periodontitis is significantly lower than that in individuals with healthy periodontal condition. Ma et al .…”
Section: Discussionmentioning
confidence: 99%